Design a photovoltaic system based on maximum power point tracking under partial shading - Ma’allin, Usama Abdullahi (2019)
Photovoltaic systems have been given special attention given their long-term potential advantages. Solar panels can produce maximum power at specific operating points called maximum power points (MPP). Solar panels must work at this particular stage in order to ensure that solar panels produce maximum power and maximize efficiency. The performance of the solar photovoltaic unit is strongly affected by the level of radiation, heat and partial shading condition. The partial shedding condition is one of vectors that can affect the PV cell performance. To overcome on this problem, this project proposes photovoltaic system based on maximum power point tracking of partial shading condition. The MPPT algorithm has many methods like P&O and PSO. P&O it had limitation that is not capable to cover the multi-peaks curves. Beside that the PSO method is more effective in partial shading condition. The voltage and current of MSX60 PV module are subjected to various insolation conditions. The Particle Swarm Optimization (PSO) algorithm based MPPT has been implemented to track maximum power partial shading condition. So, in normal condition the power reach 245 W which is higher than the power under partial shading condition that reach 100 W. The PV module is designed using MATLAB/SIMULINK. The accurateness of this simulator is verified with PV module, the result is practiced during normal condition and under partial shading condition meanwhile, multiple curves of I-V and P-V will produce during normal condition and partial shading condition.